The Mahabharata in global political and social thought - Banerjee, Milinda; Strube, Julian (South Asian intellectual history, 2024)
"The Mahabharata in Global Political and Social Thought studies the role of the epic Mahabharata in shaping modern social, political, and religious thought. It positions the Mahabharata as an influential political text and explores its role in the global history of ideas. In this edited volume, the gaze extends beyond India to also focus on Japan, China, Thailand, Iran, the Arab world, Germany, and Britain. It aims to showcase how the Mahabharata helped connect India to much wider, pan-Eurasian, intellectual and political networks and demonstrates how the epic became central in globally entangled debates about religion in general and Indian religion in particular"--